Pengaruh Gaya Kepemimpinan Transformasional, Transaksional dan Paternalistik terhadap Kinerja UMKM di Kota Pangkalpinang - Hamsani Hamsani; Nanang Suryadi; Edy Suroso (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to examine the influence of transformational, transactional, and paternalistic leadership styles and to examine which leadership style has the greatest influence on the performance of MSMEs in Pangkalpinang City. This study uses a quantitative approach with a descriptive design. Data were collected through questionnaires to 100 respondents from MSMEs in Pangkalpinang City. The data were analyzed and tested using multiple linear regression. All questions/statements in the questionnaire were declared valid because the calculated r value was > r table (calculated r value = above 0.1966) while the Cronbach's Alpha value was 0.883 above 0.60, so the instrument in this study was declared reliable. The results of the study indicate a positive and significant influence between transformational leadership style (β = 0.533; t = 2.618; p = 0.010) and transactional leadership style (β = 0.394; t = 2.308; p = 0.038) on MSME performance. However, paternalistic leadership style (β = 0.192; t = 1.701; p = 0.069) has a positive but insignificant influence on MSME performance. This research is expected to benefit MSME actors so they can demonstrate behaviors that reflect transformational and transactional leadership styles and minimize authoritarian behaviors in paternalistic leadership styles.